Notes on the losses compensation of a three-phase power system with DC offset based on geometric algebras - Brdečková, Johanka; Hrdina, Jaroslav (Nonlinear Analysis: Modelling and Control, 2025)
In a three-phase symmetric power system, we propose a transformation that converts the original current to a current with minimal losses while preserving the standard constraints. The selected transformation is realized in suitable geometric algebra and is not time-dependent. The proposed transformation uses the group symmetry of conformal geometric algebra, mainly rotations and tations.